Event-Triggered Model Predictive Control for target tracking with angles-only measurements. Issue 1 (July 2017) - Merlinge, Nicolas; Piet-Lahanier, Héléne; Dahia, Karim
Abstract: This study presents the definition of a new guidance law for a UAV tracking a mobile target using angles-only measurements. The objective of the guidance scheme is to follow the target so that it remains at a given range while enhancing its observability. It is based on a combination of two simple complementary behavior guidance laws: pure pursuit and lateral maneuver. Determination of suitable maneuvers is performed using Model Predictive Control approach using a function of the angles-rate as the optimality criterion. In order to reduce energy consumption, an additional event-triggered strategy, based on the evaluation of estimation uncertainty is used to determine the time when maneuvers are needed. Numerical simulations are presented to evaluate the resulting performances of systematic and event-triggered guidance. Event-triggered MPC strategy is shown to keep an equivalent estimation accuracy as systematic maneuvers while saving energy and computation budget.